Assessing Banking Soundness of Infobank15 Index' Categories: The Impact of RGEC on Stock Return - Destri Alpiani; Radia Purbayati; Setiawan Setiawan; Darya Setia Nugraha (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Assessment of the soundness of a bank using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) shows the financial performance of a banking company for a certain period. With good performance, investors will be interested in investing in the company. This study aims to determine the effect of bank soundness on bank stock returns listed on the Indonesia Stock Exchange in the Infobank 15 Index category for the 2016-2021 period. With a purposive sampling method, 10 banks were obtained from a total population of 15. This study uses panel data multiple linear regression analysis using Eviews 12 software. The regression model chosen is the Common Effect Model (CEM). The results showed that partially Non-Performing Loans (NPL) had a significant negative effect on stock returns. Return on Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) have a significant positive effect, and Loan to Deposit Ratio (LDR) and Good Corporate Governance (GCG) have no significant effect on stock returns.